(Dis)continuity of State Identity : Germany, Japan and the Legacy of the Second World War - Jägerová, Veronika; Lehmannová, Zuzana, 1951-; Zemanová, Michaela; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
This paper explores factors which influence various policy choices vis-à-vis the reconciliation of countries whose reputation was damaged due to the injustice they committed unto other countries during the Second World War. This complex issue of achieving discontinuity of the wrongdoer’s state identity through reconciliatory policies is studied by analysing perpetrators: Nazi Germany and Imperial Japan, and their subsequent, post-war polities. Both countries are compared regarding their individual responses to the same factors of either an internal or external nature. By assessing the significance of internal and external forces throughout time, this paper seeks to answer whether the remarkable difference in trajectory between Germany and Japan following the Second World War is more of a result of domestic predispositions (national identity and culture) or external forces (the countries’ position in the changing international system, etc.). This paper seeks to answer following research question: “To what extent is the (dis)continuity of the state identity of Germany and Japan the result of internal (or external) forces?” By answering the research question, this paper utilises both a comparative method and qualitative analysis.
Vedoucí práce: Zuzana Lehmannová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: mezinárodní politika a diplomacie [obor dipl. práce]; diplomové práce; master's theses